2017
DOI: 10.15406/ijcam.2017.07.00237
|View full text |Cite
|
Sign up to set email alerts
|

The Many Biological Functions of the Alternative Cellular Energy (ACE) Pathway

Abstract: This article summarizes the known biological functions of the alternative cellular energy (ACE) pathway. It has been proposed that this pathway is powered by a natural force called KELEA (kinetic energy limiting electrostatic attraction). KELEA can be transferred to liquids, including water and body fluids. The absorption of KELEA results in a loosening and possible lengthening of the intermolecular bonding between the liquid molecules, along with an increase in the kinetic activity of the molecules. KELEA can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…14 Further studies have confirmed that the alternative cellular energy (ACE) pathway is expressed as an added dynamic or kinetic property of the body's fluids. [15][16][17][18] This energy is exchangeable with chemical energy 19,20 and can support chemical reactions including biosynthesis. 14 The energy results from the absorption into the body of an external force called KELEA (kinetic energy limiting electrostatic attraction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Further studies have confirmed that the alternative cellular energy (ACE) pathway is expressed as an added dynamic or kinetic property of the body's fluids. [15][16][17][18] This energy is exchangeable with chemical energy 19,20 and can support chemical reactions including biosynthesis. 14 The energy results from the absorption into the body of an external force called KELEA (kinetic energy limiting electrostatic attraction).…”
Section: Discussionmentioning
confidence: 99%
“…14 The energy results from the absorption into the body of an external force called KELEA (kinetic energy limiting electrostatic attraction). [15][16][17][18] Using the activation of nearby water as a measurable parameter of the level of KELEA, laughing yoga classes were shown to enhance the radiant energy fields of participating individuals. 21 Based on this and other observations, it was proposed that certain forms of fluctuating electrical activity in the brain can act as an antenna to attract KELEA into the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and other fluids can be reliably activated using various dipolar compounds that are capable of attracting KELEA into fluids. [60][61][62][63][64] Once the water is sufficiently activated, the activating compounds, referred to as enerceuticals, can be removed by repeated dilutions, filtration, decanting or other means. KELEA activated water can also be produced by sufficient exposure to an increased environmental level of KELEA as created using various devices.…”
Section: Alternative Cellular Energy (Ace) Pathwaymentioning
confidence: 99%
“…While the ACE pathway overlaps with food metabolism in promoting various cellular activities, it can support cellular functions beyond those provided by food [25]. Specifically, the ACE pathway provides an effective non-immunological defense against viral and bacterial infections [26]- [31].…”
Section: Introductionmentioning
confidence: 99%